Using visual text analytics to examine broadcast interviewing. (March 2016) - Angus, Daniel; Fitzgerald, Richard; Atay, Christina; Wiles, Janet
Abstract: Broadcast interview hosts are increasingly adopting hybrid forms of interview through the utilization of interview techniques from different genres within the one interview (Ekström and Kroon Lundell, 2011; Montgomery, 2008 ). Methods that can visually represent interviews in their entirety have the potential to assist in tracking and tracing genre shifts within a single interview. In this paper we examine traditional genres and hybrid forms of broadcast interviewing using a visual text analytic software Discursis (Angus et al., 2013, 2012a, 2012b ). Discursis provides visual representations of whole interviews at-a-glance as well as the ability to focus into particular sections for closer analysis. Drawing on a corpus of 101 interviews from a single television program, this study examines if Discursis can meaningfully visually represent forms of interviewing genres (Montgomery, 2008 ) and highlight where shifting techniques (Ekström and Kroon Lundell, 2011 ) are used within a single interview. Highlights: Discursis can provide overviews of the topical interaction in broadcast interviews. Expert manual coding matched Discursis visual features. Computer-aided analysis can allow researchers to analyze more content. Discursis is particularly useful for analyzing hybrid forms of broadcast interview.